Age- and sex-specific analysis of patients with embolic stroke of undetermined source. (8th August 2017) - Ntaios, George; Lip, Gregory Y.H.; Vemmos, Konstantinos; Koroboki, Eleni; Manios, Efstathios; Vemmou, Anastasia; Rodríguez-Campello, Ana; Cuadrado-Godia, Elisa; Roquer, Jaume; Arnao, Valentina; Caso, Valeria; Paciaroni, Maurizio; et al.
Abstract : Objective: To investigate whether the correlation of age and sex with the risk of recurrence and death seen in patients with previous ischemic stroke is also evident in patients with embolic stroke of undetermined source (ESUS). Methods: We pooled datasets of 11 stroke registries from Europe and America. ESUS was defined according to the Cryptogenic Stroke/ESUS International Working Group. We performed Cox regression and Kaplan-Meier product limit analyses to investigate whether age (<60, 60–80, >80 years) and sex were independently associated with the risk for ischemic stroke/TIA recurrence or death. Results: Ischemic stroke/TIA recurrences and deaths per 100 patient-years were 2.46 and 1.01 in patients <60 years old, 5.76 and 5.23 in patients 60 to 80 years old, 7.88 and 11.58 in those >80 years old, 3.53 and 3.48 in women, and 4.49 and 3.98 in men, respectively. Female sex was not associated with increased risk for recurrent ischemic stroke/TIA (hazard ratio [HR] 1.15, 95% confidence interval [CI] 0.84–1.58) or death (HR 1.35, 95% CI 0.97–1.86). Compared with the group <60 years old, the 60- to 80- and >80-year groups had higher 10-year cumulative probability of recurrent ischemic stroke/TIA (14.0%, 47.9%, and 37.0%, respectively, p < 0.001) and death (6.4%, 40.6%, and 100%, respectively, p < 0.001) and higher risk for recurrent ischemic stroke/TIA (HR 1.90, 95% CI 1.21–2.98 and HR 2.71, 95% CI 1.57–4.70, respectively) and death (HR 4.43, 95% CI 2.32–8.44 and HR 8.01, 95% CI 3.98–16.10, respectively). Conclusions: Age, but not sex, is a strong predictor of stroke recurrence and death in ESUS. The risk is ≈3- and 8-fold higher in patients >80 years compared with those <60 years of age, respectively. The age distribution in the ongoing ESUS trials may potentially influence their power to detect a significant treatment association.